High-temperature-bearing nickel-based powder high-temperature alloy and preparation method thereof
By adjusting the ratio and heat treatment process of multiple alloy elements, a high-temperature nickel-based powder high-temperature alloy was developed, which solved the problem of maintaining high temperature strength and tissue stability at higher temperatures, and achieved excellent mechanical properties and creep Resistance to meet the high-temperature structural materials needs of aircraft engines.
Patent Information
- Application Number
- CN202411323790.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-11
AI Technical Summary
The development of powdered high-temperature alloys that can work at higher temperatures should not only improve the high-temperature strength of the material, but also maintain tissue stability and process performance, so as to avoid performance degradation and increased processing difficulty caused by higher alloying.
By comprehensively adjusting the ratio of more than 10 alloy elements in powder high-temperature alloys, a reasonable γ' precipitation phase content and solid solution temperature are designed, combined with appropriate W element content and Cr, Mo, and Nb element control, Hf elements are added to enhance crystals and select the appropriate solution heat treatment temperature and insulation time to ensure that the material has excellent mechanical properties and tissue stability at high temperatures.
It achieves a high yield strength and significantly improved creep resistance at 850°C. The high-temperature tissue stability and process performance of the material can be taken into account, meeting the needs of high-temperature bearing structural materials in aerospace engines and aerospace power systems.
Smart Images

Figure CN119410958A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high temperature alloys, in particular to a nickel-based powder high temperature alloy for high temperature rotating parts of complex structures of aviation and aerospace engines, and a preparation method and application thereof. Background Art
[0002] The applicant has found through research that the operating temperature of high-temperature rotating parts in aircraft engines determines the key performance of aircraft engines, such as thermal efficiency and thrust-to-weight ratio. Under extremely high speeds and complex aerodynamic conditions, high-temperature rotating parts must withstand extremely high centrifugal forces and complex fatigue loads. In addition, high-temperature rotating parts without thermal barrier coating protection are exposed to oxidative corrosion environments, which will also reduce their lifespan and reliability. Therefore, the materials used to manufacture high-temperature rotating parts need to have excellent mechanical properties such as high-temperature tensile, creep, fatigue, durability, damage tolerance, good high-temperature structural stability, and anti-oxidation and corrosion properties at high temperatures.
[0003] For high-temperature rotating parts of the disk type, the main preparation methods are "casting-forging" and "powder metallurgy" process routes. The former uses deformed high-temperature alloys, and after multiple smelting, casts large-sized ingots. After the ingots are opened, fine-grained structures are obtained, and then the disks are obtained by die forging. The "powder metallurgy" process obtains fine powders through atomization powder making, and then obtains ingots with fine structures for die forging through hot isostatic pressing and hot extrusion processes. The material solidifies rapidly during the atomization powder making process, which greatly reduces or even eliminates the segregation of elements, and finally obtains a more uniform material structure. Although the materials prepared by the "casting-forging" process can achieve the same static strength as the disk materials prepared by the powder metallurgy route, due to the macroscopic component segregation, the structure is not uniform, and the material's fatigue and other high-temperature long-term service performance are significantly inferior to those of powder alloys. In addition, in order to achieve higher material properties and service temperatures, the alloying degree of high-temperature alloys is higher (containing more types and larger amounts of alloying elements), and the disadvantages of element segregation and uneven structure in the "casting-forging" process are more serious. Therefore, turbine disks that require high reliability and long life are all produced using powder metallurgy technology.
[0004] As engines pursue high thrust-to-weight ratio / power-to-weight ratio and economy, powder high-temperature alloy turbines need to be able to serve at higher temperatures (e.g. 850°C and above). To this end, it is necessary to develop powder high-temperature alloy materials with higher temperature bearing capacity (i.e., having the same tensile strength at higher temperatures, and having a longer creep life under the same temperature and stress conditions). Summary of the invention
[0005] The technical problems faced by the development of powder high-temperature alloys are: the development of powder high-temperature alloys that can work at higher temperatures can improve the high-temperature strength of the material by increasing the alloying degree of the material and obtaining more γ' precipitation phases with higher strength and higher solid solution temperature. However, a higher degree of alloying affects the high-temperature structural stability of the material (i.e., it is easier to produce phases such as TCP that are harmful to performance at high temperatures), which is not conducive to the long-term service of the material at high temperatures. In addition, higher material strength reduces the material's thermal mechanical processing window, making forging, heat treatment and other processes difficult.
[0006] To this end, the technical solution of the present invention is to obtain a preferred material composition space by comprehensively adjusting the ratio of more than 10 alloying elements in the powder high-temperature alloy. First, the content of Al, Ti, Nb, and Ta elements is designed to obtain a higher γ' precipitation phase content and a higher γ' precipitation phase solid solution temperature. Taking into account the strength and process performance of the material, the γ' precipitation phase content is set to ~60% (room temperature), and the solid solution temperature of the γ' precipitation phase is set to 1170℃~1190℃. Even at a service temperature of 850℃, the content of the γ' precipitation phase of such a material is still about 57%, which can provide sufficient precipitation phase strengthening. In addition, in order to further improve the high-temperature strength of the material, the content of the W element is also increased to ensure the effect of the solid solution strengthening mechanism. In service at higher temperatures, the material also needs to have good high-temperature structural stability, that is, as little TCP and other phases that are harmful to performance as possible are precipitated during long-term service. To this end, the present invention controls the content of Cr, Mo, and Nb elements in the alloy. In order to take into account the material cost, expensive elements such as Re, Ru, Os, and Pt are not included. Due to the reduction of Cr content, the material's anti-oxidation and anti-corrosion properties at high temperatures are lost. In equipment that has been in service for a long time, it can be used in conjunction with a high-temperature anti-corrosion coating. Furthermore, in order to improve the grain boundary strength of the material, a certain amount of Hf element is added to the material.
[0007] In order to ensure the process performance of the material, especially the forging formability, the difference between the solution temperature of the γ' precipitation phase in the material and the initial melting temperature of the material is considered in the alloy design. Although this interval is not the actual forging temperature window of the material, its size can represent the size of the forging process window of the material to a certain extent. The size of the window in the present invention is at least 50°C. After forging, the powder high-temperature alloy disc also needs to be heat treated to obtain an optimized structure. Since it is necessary to take into account the tensile strength and creep resistance at high temperature, the present invention chooses to heat treat the material at a temperature higher than the solution temperature of the γ' precipitation phase. Such a heat treatment can obtain a coarse-grained structure that has a significant effect on the improvement of creep resistance, and the average grain size is maintained at about 20μm to 100μm by selecting a suitable solution heat treatment temperature and holding time. Since the content of the γ' precipitation phase in the alloy of the present invention is still high at a service temperature of 850°C, even the coarse-grained structure has a high tensile strength. In addition, the strength of the powder high-temperature alloy is related to the size of the γ' precipitation phase, and the size of the γ' precipitation phase is related to the cooling rate after the solution heat treatment. A high cooling rate can obtain a finer γ' precipitate phase, thereby improving the strength and creep resistance of the material. However, for large-scale parts, due to the large mass and overall heat capacity, it is difficult to increase the cooling rate of the parts after solution heat treatment. In addition, for alloys with higher strength, if forced cooling is performed externally during the cooling process after solution to increase the cooling rate, problems such as quenching cracking and large residual stress will also occur due to higher thermal stress. Therefore, a powder high-temperature alloy material with higher strength and creep resistance is needed even at a lower cooling rate. In the present invention, the alloy comprehensively optimizes the elemental organization and ratio of the material so that the γ' precipitate phase has a lower mismatch with γ and has a higher antiphase domain boundary energy.
[0008] Through a lot of research, iteration and optimization, the present invention provides a high temperature-bearing nickel-based powder high-temperature alloy, having the following mass composition elements: Cr 6.0%-9.0%, Co 15.0%-16.0%, W 5.0%-8.0%, Mo 1.0%-2.0%, Al 3.0%-4.0%, Ti 3.0%-4.0%, Nb 3.0%-3.5%, Ta 2.0%-3.0%, Zr0.0%-0.1%, C 0.02%-0.3%, B 0.02%-0.03%, Hf 0.0%-0.5%, Fe 0.0%-1.0%, and the balance is Ni, other trace elements beneficial to high-temperature alloys, and unavoidable trace or impurity elements.
[0009] On the other hand, the present invention also provides a method for preparing the above nickel-based powder high-temperature alloy. The method comprises the following steps:
[0010] The material and turbine disk preparation of the present invention includes six steps.
[0011] In the first step, the materials are prepared according to the element ratio of the invented alloy, and the master alloy rod is prepared by vacuum induction melting process.
[0012] In the second step, the master alloy rod is prepared into high-temperature alloy powder by argon atomization or rotating electrode powder making process.
[0013] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0014] The fourth step is to hot isostatically press the alloy powder sheath after sealing. In order to obtain a structure suitable for subsequent hot extrusion and isothermal forging, the hot isostatic pressing temperature of the alloy in the present invention is 1120℃~1200℃, the pressure is 120MPa~140MPa, and the duration is 2h~6h). Through this step, the powder can be solidified to obtain a dense alloy ingot. Among them, the ingot that is directly forged later should be hot isostatically pressed at a lower temperature to avoid excessive growth of the grain size.
[0015] The fifth step is to select a suitable thermal process to prepare the blank into a disc blank according to the size and shape of the final part. Since the nickel-based powder high-temperature alloy provided by the present invention has both excellent high-temperature performance and good process compatibility, it is suitable for three process routes at the same time: ① directly heat-treating the hot isostatically pressed ingot obtained in the fourth step; ② isothermally forging the ingot obtained in the fourth step, and then heat-treating it; ③ preparing the hot isostatically pressed billet into an ultrafine grained rod by extrusion, and then performing subsequent isothermal forging and heat treatment. By selecting appropriate process parameters, the alloys of the present invention prepared by the above three methods have the same mechanical properties.
[0016] The sixth step is to process the disc blank prepared in the fifth step into the final part.
[0017] The advantages and beneficial effects of the present invention are:
[0018] The powder high-temperature alloy with the above-mentioned composition and organizational characteristics provided by the present invention has a yield strength of 1150MPa to 1300MPa at room temperature, and a yield strength of 850MPa to 1050MPa at 850°C. Compared with the existing powder high-temperature alloy ME501, its yield strengths at 760°C and 815°C are 1041MPa and 903MPa, respectively. The nickel-based powder high-temperature alloy provided by the present invention can achieve the same strength at 850°C. Compared with the alloy in patent CN 110241331B, which has a yield strength of 1040MPa at 815°C, the nickel-based powder high-temperature alloy provided by the present invention can achieve the same strength at 850°C.
[0019] In creep tests at 760°C and 552MPa, NASA Alloy 1 alloy took 207 hours to reach a creep strain of 0.3%, and the second-generation single crystal alloy CMSX-4 took 230 hours. The alloy of the present invention takes more than 1400 hours to reach a creep strain of 0.2% (the creep deformation life is increased by at least 7 times), showing significantly superior creep resistance. The material provided by the present invention was creep tested at 850°C and 330MPa, and the fracture life can reach more than 300 hours. In contrast, other currently more advanced nickel-based powder high-temperature alloys can only obtain a comparable creep fracture life under the conditions of 800°C to 830°C and 330MPa. From the above comparison, it can be seen that the nickel-based powder high-temperature alloy provided by the present invention has excellent high-temperature mechanical properties, and its temperature bearing capacity is significantly improved, which meets the demand for high temperature bearing structural materials for rotating parts in aero-engines and aerospace power systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. It is obvious that the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 A photograph of a uniform equiaxed crystal structure with a grain size of about 20 μm to 100 μm of the material prepared by the method of the present invention;
[0022] Figure 2 It is a secondary γ' precipitation phase in the crystal with a size of about 150nm to 300nm in the material prepared by the method of the present invention. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other, and the embodiments can refer to and quote each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0025] Table 1 shows typical alloy compositions in the present invention.
[0026] Table 1
[0027]
[0028]
[0029] For Example 1, the preparation steps are as follows:
[0030] In the first step, the ingredients are prepared according to the element ratio of component 1 in the embodiment, and the master alloy rod is prepared by vacuum induction melting process.
[0031] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0032] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0033] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package at a temperature of about 1150°C, a pressure of about 140 MPa, and a duration of 3 hours.
[0034] The fifth step is to perform solution heat treatment at 1230℃ / 2h and aging heat treatment at 875℃ / 4h on the material after hot isostatic pressing.
[0035] After this step, the analysis and testing of the blank showed that the material had a uniform equiaxed crystal structure (such as Figure 1 As shown in Figure 2), the average grain size is about 75 μm, the average size of the secondary γ′ precipitate phase in the crystal is about 200 nm, and there is also a small amount of tertiary γ′ precipitate phase, which together account for about 60.5% (as shown in Figure 2). Figure 2 The yield strength at 850°C is 890MPa, and the creep rupture life at 850°C and 330MPa is more than 300 hours.
[0036] For Example 2, the preparation steps are as follows:
[0037] In the first step, the materials are prepared according to the element ratio of component 2 in the embodiment, and the master alloy rod is prepared by vacuum induction melting process.
[0038] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0039] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0040] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package. The hot isostatic pressing temperature is about 1120°C, the pressure is about 140MPa, and the duration is 3 hours.
[0041] The fifth step is to perform solution heat treatment at 1210℃ / 2h and aging heat treatment at 875℃ / 4h on the hot isostatic pressed material.
[0042] The analysis and testing of the blank after this step showed that the material had a uniform equiaxed crystal structure, an average grain size of about 50 μm, an average size of the secondary γ′ precipitation phase within the crystal of about 220 nm, and a small amount of tertiary γ′ precipitation phase. The total proportion of the two was about 60.5%, the yield strength at 850°C was 900 MPa, and the creep rupture life at 850°C and 330 MPa was more than 300 hours.
[0043] For Example 3, the preparation steps are as follows:
[0044] In the first step, the materials are prepared according to the element ratio of component 2 in the embodiment, and the master alloy rod is prepared by vacuum induction melting process.
[0045] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0046] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0047] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package. The hot isostatic pressing temperature is about 1120°C, the pressure is about 140MPa, and the duration is 3 hours.
[0048] In the fifth step, the hot isostatically pressed material is isothermally forged at about 1100°C, and then the forged billet is solution treated at 1210°C / 2h and aging treated at 875°C / 4h.
[0049] The analysis and testing of the blank after this step shows that this embodiment has similar organization and performance to that of Embodiment 2. The material has a uniform equiaxed crystal organization, an average grain size of about 50 μm, an average size of the secondary γ′ precipitation phase within the crystal of about 200 nm, and a small amount of tertiary γ′ precipitation phase. The total proportion of the two is about 60.5%. The yield strength at 850°C is 900 MPa, and the creep rupture life at 850°C and 330 MPa is more than 300 hours.
[0050] For Example 4, the preparation steps are as follows:
[0051] In the first step, the materials are prepared according to the proportion of the three elements in the embodiment, and the master alloy rod is prepared by vacuum induction melting process.
[0052] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0053] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0054] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package at a temperature of 1120°C, a pressure of about 140 MPa, and a duration of 3 hours.
[0055] In the fifth step, the hot isostatically pressed material is isothermally forged at about 1100°C, and then the forged billet is solution treated at 1210°C / 2h and aging treated at 875°C / 4h.
[0056] The analysis and testing of the blank after this step shows that this embodiment has similar structure and performance to that of Embodiment 2. The material has a uniform equiaxed crystal structure, an average grain size of about 50 μm, an average size of the secondary γ′ precipitation phase within the crystal of about 180 nm, and a small amount of tertiary γ′ precipitation phase. The total proportion of the two is about 59.5%. The yield strength at 850°C is 880 MPa, and the creep rupture life at 850°C and 330 MPa is more than 300 hours.
[0057] For Example 5, the preparation steps are as follows:
[0058] In the first step, the materials are prepared according to the proportion of the three elements in the embodiment, and the master alloy rod is prepared by vacuum induction melting process.
[0059] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0060] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0061] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package at a temperature of 1120°C, a pressure of about 140 MPa, and a duration of 3 hours.
[0062] In the fifth step, the material after hot isostatic pressing is hot extruded at about 1100°C to obtain fine-grained extruded rods; the rod blank is then isothermally forged at about 1100°C, and the forged blank is solution heat treated at 1210°C / 2h and aging heat treated at 875°C / 4h.
[0063] After this step, the analysis and testing of the blank material show that this embodiment has similar structures and properties to those of embodiment 4. This is because the extrusion process only changes the deformation process properties of the material, making it easier to be forged into complex shapes and structures. The final properties of the material are still determined by the final heat treatment system.
[0064] For Example 6, the preparation steps are as follows:
[0065] In the first step, the ingredients are prepared according to the ratio of the four elements in the embodiment, and the master alloy rod is prepared by vacuum induction melting process.
[0066] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0067] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0068] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package at a temperature of 1150°C, a pressure of about 140 MPa, and a duration of 3 hours.
[0069] In the fifth step, the hot isostatic pressed billet is then subjected to a solution heat treatment at 1230°C / 2h and an aging heat treatment at 815°C / 8h.
[0070] The analysis and testing of the blank after this step shows that the material of this embodiment has a uniform equiaxed crystal structure, an average grain size of about 80 μm, an average size of the secondary γ′ precipitation phase in the crystal of about 250 nm, and a small amount of tertiary γ′ precipitation phase, the total proportion of the two is about 60%, the yield strength at 850°C is 880 MPa, and the creep rupture life at 850°C and 330 MPa is more than 300 hours. The time taken to reach 0.2% creep strain at 760°C and 552 MPa is more than 1000 hours.
[0071] For Example 7, the preparation steps are as follows:
[0072] In the first step, the ingredients are prepared according to the proportion of the five elements in the embodiment, and a master alloy rod is prepared by a vacuum induction melting process.
[0073] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0074] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0075] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package at a temperature of 1150°C, a pressure of about 140 MPa, and a duration of 3 hours.
[0076] In the fifth step, the hot isostatically pressed material is isothermally forged at about 1100°C, and then the forged billet is subjected to a solution heat treatment at 1215°C / 2h and an aging heat treatment at 875°C / 2h.
[0077] The analysis and testing of the blank after this step shows that the material of this embodiment has a uniform equiaxed crystal structure, an average grain size of about 60 μm, an average size of the secondary γ′ precipitation phase in the crystal of about 200 nm, and a small amount of tertiary γ′ precipitation phase. The total proportion of the two is about 60.5%, the yield strength at 850°C is about 1000 MPa, and the creep rupture life at 850°C and 330 MPa is more than 300 hours.
[0078] For Example 8, the preparation steps are as follows:
[0079] In the first step, the ingredients are prepared according to the proportion of the six elements in the embodiment, and the master alloy rod is prepared by vacuum induction melting process.
[0080] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0081] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0082] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package at a temperature of 1150°C, a pressure of about 140 MPa, and a duration of 3 hours.
[0083] In the fifth step, the hot isostatic pressed billet is then subjected to a solution heat treatment at 1200°C / 2h and an aging heat treatment at 815°C / 8h.
[0084] The analysis and testing of the blank after this step shows that the material of this embodiment has a uniform equiaxed crystal structure, an average grain size of about 30 μm, an average size of the secondary γ′ precipitation phase in the crystal of about 150 nm, and a small amount of tertiary γ′ precipitation phase. The total proportion of the two is about 60%, the yield strength at 850°C is about 1050 MPa, and the creep rupture life at 850°C and 330 MPa is more than 300 hours.
[0085] For Example 9, the preparation steps are as follows:
[0086] In the first step, the ingredients are prepared according to the proportion of the seven elements in the embodiment, and a master alloy rod is prepared by a vacuum induction melting process.
[0087] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0088] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0089] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package at a temperature of 1120°C, a pressure of about 140 MPa, and a duration of 3 hours.
[0090] In the fifth step, the hot isostatically pressed material is isothermally forged at about 1100°C, and then the forged billet is solution treated at 1215°C / 2h and aging treated at 850°C / 4h.
[0091] The analysis and testing of the blank after this step shows that the material of this embodiment has a uniform equiaxed crystal structure, an average grain size of about 50 μm, an average size of the secondary γ′ precipitation phase in the crystal of about 200 nm, and a small amount of tertiary γ′ precipitation phase. The total proportion of the two is about 60%, the yield strength at 850°C is about 950 MPa, the creep rupture life at 850°C and 330 MPa is more than 300 hours, and the time taken to reach a creep strain of 0.2% at 760°C and 552 MPa is more than 1400 hours.
[0092] For Example 10, the preparation steps are as follows:
[0093] In the first step, the ingredients are prepared according to the proportion of the seven elements in the embodiment, and a master alloy rod is prepared by a vacuum induction melting process.
[0094] In the second step, the master alloy rod is prepared into high-temperature alloy powder by using argon atomization powder making process.
[0095] The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening.
[0096] The fourth step is to perform hot isostatic pressing on the sealed alloy powder package. The hot isostatic pressing temperature is about 1120°C, the pressure is about 140MPa, and the duration is 3 hours.
[0097] The fifth step is to hot extrude the material after hot isostatic pressing at about 1100°C to obtain fine-grained extruded rods; then the rod blank is isothermally forged at about 1100°C, and then the forged blank is solution heat treated at 1215°C / 2h and aging heat treated at 850°C / 4h.
[0098] After this step, the analysis and testing of the blank material show that this embodiment has similar structures and properties to those of embodiment 7. This is because the extrusion process only changes the deformation process properties of the material, making it easier to be forged into complex shapes and structures. The final properties of the material are still determined by the final heat treatment system.
[0099] It should be noted that the above-mentioned process operations can be applied in combination to different degrees. For the sake of simplicity, the implementation methods of various combinations are not described in detail. Technical personnel in this field can flexibly adjust the order of the above-mentioned operating steps according to actual needs, or flexibly combine the above-mentioned steps.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should all be covered within the protection scope of the present invention.
Claims
1. A high temperature bearing nickel-based powder high temperature alloy, characterized in that: Includes the following elements by mass composition: Cr 6.0%~9.0%, Co 15.0%~16.0%, W 5.0%~8.0%, Mo 1.0%~2.0%, Al 3.0%~4.0%, Ti3.0%~4.0%, Nb 3.0%~3.5%, Ta 2.0%~3.0%, Zr 0.0%~0.1%, C 0.02%~0.3%, B 0.02%~0.03%, Hf 0.0%~0.5%, Fe 0.0%~1.0%, and the balance is Ni and other impurity elements.
2. The high temperature bearing nickel-based powder high temperature alloy according to claim 1, characterized in that: The mass composition of each element is one or more of the following:
3. The high temperature bearing nickel-based powder high temperature alloy according to any one of claims 1 to 3, characterized in that: The high temperature-bearing nickel-based powder high-temperature alloy is used to manufacture compressor disks, turbine disks, and blade disks of aircraft engines, high-pressure compressors, and high-pressure turbines.
4. A method for preparing a high temperature bearing nickel-based powder high temperature alloy according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: The first step is to prepare a master alloy rod by vacuum induction melting process according to the element ratio of the high temperature bearing nickel-based powder high temperature alloy in any one of claims 1 to 3; In the second step, the master alloy rod is prepared into high temperature alloy powder by argon atomization or rotary electrode powder making process; The third step is to screen the prepared high-temperature alloy powder, degas and package the alloy powder with a particle size of -270 mesh after screening, and seal the package opening; The fourth step is to perform hot isostatic pressing on the sealed alloy powder package at a temperature of 1120°C to 1200°C, a pressure of 120MPa to 140MPa, and a time of 2 to 6 hours to solidify the powder and obtain a dense alloy ingot; The fifth step is to perform hot extrusion, isothermal forging, solid solution and aging heat treatment on the alloy ingot according to the size and shape of the final product to obtain a disc blank. The sixth step is to prepare the disc blank into the final part through machining. In the seventh step, high temperature anti-corrosion coating is applied to the surface of the parts.
5. The method according to claim 5, characterized in that: In the first step: The content of the γ' precipitation phase of the master alloy rod is 60% at room temperature, and the solid solution temperature of the γ' precipitation phase is 1170°C to 1190°C.
6. The method according to claim 4, characterized in that In said fifth step: The solution heat treatment temperature is 1200-1215°C, the holding time is 1h-2h, the cooling rate of the material after heat treatment and holding is about 0.2°C / s-3.0°C / s, the aging heat treatment temperature is 815°C-875°C, and the holding time is 4h-16h.
7. The method according to claim 5, characterized in that The nickel-based powder high-temperature alloy obtained based on the above composition and process has a supersolution coarse-grained structure with an average grain size of about 20μm to 100μm and an intracrystalline secondary γ′ precipitation phase with an average size of about 150nm to 300nm.
8. The method according to claim 5, characterized in that in: The nickel-based powder high-temperature alloy obtained based on the above composition and process can have a yield strength of 1150MPa to 1300MPa when tested at room temperature, and a yield strength of 850MPa to 1050MPa when tested at 850°C, and has excellent creep resistance at 760°C to 850°C.
9. The method according to any one of claims 5 to 9, characterized in that: in: The high temperature bearing nickel-based powder high temperature alloy was creep tested under the conditions of 850℃ and 330MPa, and the fracture life exceeded 300 hours.
Citation Information
Patent Citations
Nickel-based powder superalloys, their preparation methods and applications
CN110241331B
Cited By
Nickel-cobalt-based alloy, nickel-cobalt-based alloy component using the same, and method for manufacturing the same.
JP7903888B2
JPWO2024101048A1